PETROLEUM PRODUCTS IN AQUATIC ENVIRONMENTS - Кочмарський, В.З.; Кочмарський, О.В. (Modern engineering and innovative technologies, 2023)
In the aquatic environment petroleum products (PP) are in different migration forms: in the homogeneous phase in the form of droplets of various sizes and films with thickness from 1 to 200 microns; in the emulsified form; in the form of molecular solutio